High-temperature polymer based magnetoelectric nanocomposites. (March 2015) - Maceiras, A.; Martins, P.; Gonçalves, R.; Botelho, G.; Venkata Ramana, E.; Mendiratta, S.K.; San Sebastián, M.; Vilas, J.L.; Lanceros-Mendez, S.; León, L.M.
Graphical abstract: Highlights: High temperature magnetoelectric polymer base composites are reported. The nanocomposite is based on polyimides and CoFe2 O4 nanoparticles. The magnetization response is determined by the CFO nanoparticle content. The piezoelectric response of the 0CN2CN polymer matrix is ≈11 pC N −1 . The α 33 value (0.8 mV cm −1 Oe −1 ) is stable over time and decrease above 130 °C. Abstract: The use of polymer based magnetoelectric materials for sensing and actuation applications has been the subject of increasing scientific and technological interest. One of the drawbacks to be overcome in this field is to increase the temperature range of application above 100 °C. In this way, a nanocomposite material composed by a mixture of two aromatic diamines, 1, 3-bis-2-cyano-3-(3 aminophenoxy)phenoxybenzene (diamine 2CN) and 1, 3-bis(3-aminophenoxy)benzene (diamine 0CN) and CoFe2 O4 (CFO) nanoparticles was designed, fabricated and successfully tested for high temperature magnetoelectric applications. Results revealed that CFO nanoparticles are well distributed within the 0CN2CN polymer matrix and that the addition of CFO nanoparticles does not significantly alter the polyimides structure. The magnetization response of the composite is determined by the CFO nanoparticle content. The piezoelectric response of the 0CN2CN polymer matrix (≈11 pC N −1 ) and the maximum α 33 value (0.8 mV cm −1 Oe −1 ) are stable over time and decrease only when the composite is subjected to temperatures above 130 °C. Strategies to further improve the ME response are also discussed.